Co-initiation of continuous renal replacement therapy, peritoneal dialysis, and extracorporeal membrane oxygenation in neonatal life-threatening hyaline membrane disease: A case report. Issue 4 (January 2019) - Li, Guanhua; Zhang, Li; Sun, Yunxia; Chen, Jimei; Zhou, Chengbin
Abstract: Rationale: Extracorporeal membrane oxygenation (ECMO) is a well-known technique to provide cardio-pulmonary support. Although continuous renal replacement therapy (CRRT) is frequently indicated, the need for faster fluid removal as the primary indication for ECMO is uncommon. Experiences on concomitant applications of ECMO, peritoneal dialysis (PD) and CRRT in neonates are relatively limited. Patient concerns: We report a 2-day-old male neonate with life-threatening hyaline membrane disease (HMD), accompained by severe systemic fluid retention, sepsis and abdominal compartment syndrome. Diagnosis: Hyaline membrane disease (HMD), neonatal respiratory distress syndrome, sepsis, capillary leakage syndrome, and abdominal compartment syndrome. Intervention: Veno-arterial ECMO, CRRT, and PD were synchronously initiated for the sake of faster fluid removal possible. Outcomes: The infant was successfully weaned from ECMO circuit and fluid overload was greatly improved four days after extracorporeal life support (ECLS), without major complications. Lessons: Initiation of CRRT and PD during ECMO therapy is effective and safe to release fluid overload in neonates, and severe complications are absent. When a neonate requires dialysis of urgency, ECMO offers assured vascular access to hemodialysis, allowing faster fluid removal.